THE ECO-ORIENTED VOCATIONAL TRAINING OF FUTURE PLASTERERS-TILERS (Innovative professional education, 2024)
The importance of applying eco-oriented construction technologies, especially in the post-war period of reconstruction of Ukraine, is revealed. Ways of implementing eco-oriented training of vocational (vocational-technical) educational institutions, particularly in the profession of plasterer-tiler, are outlined. It is argued that environmental requirements for cladding work include the following three groups: organizational, technological, and personal, and the essence of each is revealed.
Keywords: eco-oriented vocational training, “green technologies”, plasterer-tiler, ecological competence, ecological education